Two new species of Jacquemontia Choisy (Convolvulaceae) endemic to Bahia, Brazil - Buril, Maria Teresa; Alves, Marccus (Phytotaxa, 2012)
Two new shrubby species of Jacquemontia (J. staplesii Buril, J. grisea Buril), endemic to Bahia, Brazil, are described. Their morphological affinities are discussed and illustrations are provided.